Le Brexit au Royaume-Uni : vers une évolution du rôle du Speaker à la Chambre des Communes ? - Damien Connil (Revue Française de Civilisation Britannique)
While Brexit has particularly highlighted the role of the Speaker in the conduct of the business and debate of the House of Commons, the sequence alone probably does not explain the possible evolution of this role. The issue goes beyond Brexit, revealing changes that run more broadly through the UK’s political and institutional system and reflecting new questions about the place and function of Parliament. In this perspective/context, the Speaker has emerged as a key player in British political and parliamentary life.